Preliminary system design for the development of CubeSat with GNSS-reflectometry (GNSS-R) payload for monitoring sea level change - Haile, Helen (2025)
Global warming is causing a rapid rise in sea levels. This is particularly pressing as the impacts are causing flooding, salinisation, extreme weather and sea temperature, and threatening food security. The impacts are particularly severe for communities in the global south and developing countries due to significant social and economic injustice. With approximately 600 million people living in coastal regions globally, the potential submerges in this area could lead to further economic impact and increase the social and economic effects felt in the global south and coast area.